Characterization of esophageal motor activity, gastroesophageal reflux, and evaluation of prokinetic effectiveness in mechanically ventilated critically ill patients: a high-resolution impedance manometry study - Balihar, Karel; Kotyza, Jan; Zdrhova, Lucie; Kozeluhova, Jana; Krcma, Michal; Matejovic, Martin (Critical care (London, England), 2021)
BACKGROUND: Motility disorders of upper gastrointestinal tract are common in critical illness and associated with significant clinical consequences. However, detailed quantitative and qualitative analyses of esophageal motor functions are lacking. Therefore, we aimed to characterize the key features of esophageal motility functions using high-resolution impedance manometry (HRIM) and to evaluate an objective link between esophageal motor patterns, gastric emptying, and gastroesophageal reflux. We also studied the prokinetic effects of metoclopramide. METHODS: We prospectively performed HRIM for 16 critically ill hemodynamically stable patients. Patients were included if they had low gastric volume (LGV; < 100 mL/24 h, n = 8) or high gastric volume (HGV; > 500 mL/24 h, n = 8). The HRIM data were collected for 5 h with intravenous metoclopramide administration (10 mg) after the first 2 h. RESULTS: The findings were grossly abnormal for all critically ill patients. The esophageal contraction vigor was markedly increased, indicating prevailing hypercontractile esophagus. Ineffective propulsive force was observed for 73% of esophageal activities. Panesophageal pressurization was the most common pressurization pattern (64%). Gastroesophageal reflux predominantly occurred with transient lower esophageal sphincter relaxation. The common features of the LGV group were a hyperreactive pattern, esophagogastric outflow obstruction, and frequent reflux. Ineffective motility with reduced lower esophageal sphincter tone, and paradoxically fewer reflux episodes, was common in the HGV group. Metoclopramide administration reduced the number of esophageal activities but did not affect the number of reflux episodes in either group. CONCLUSION: All critically ill patients had major esophageal motility abnormalities, and motility patterns varied according to gastric emptying status. Well-preserved gastric emptying and maintained esophagogastric barrier functions did not eliminate reflux. Metoclopramide failed to reduce the number of reflux episodes regardless of gastric emptying status. Trial registration ISRCTN, ISRCTN14399966. Registered 3.9.2020, retrospectively registered. https://www.isrctn.com/ISRCTN14399966 .
Keywords: umělé dýchání; Female; Prokinetics; APACHE; kritický stav; Gastroesophageal reflux; manometrie; ženské pohlaví; Esophageal dysfunction; pohybová aktivita; horní gastrointestinální trakt; lidé; Upper Gastrointestinal Tract; gastroezofageální reflux; Manometry; Gastroesophageal Reflux; Critical illness; Esophagus; prospektivní studie; Male; Aged; Prospective Studies; index tělesné hmotnosti; High-resolution impedance manometry; Motor Activity; lidé středního věku; ezofágus; senioři; mužské pohlaví; Body Mass Index; Respiration, Artificial; Middle Aged; Critical Illness; Humans